2017
DOI: 10.1038/s41598-017-06079-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of Australian and international isolates of Salmonella Typhimurium: correlation of core genome evolution with CRISPR and prophage profiles

Abstract: Salmonella enterica subsp enterica serovar Typhimurium (S. Typhimurium) is a serovar with broad host range. To determine the genomic diversity of S. Typhimurium, we sequenced 39 isolates (37 Australian and 2 UK isolates) representing 14 Repeats Groups (RGs) determined primarily by clustered regularly interspaced short palindromic repeats (CRISPR). Analysis of single nucleotide polymorphisms (SNPs) among the 39 isolates yielded an average of 1,232 SNPs per isolate, ranging from 128 SNPs to 11,339 SNPs relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 42 publications
2
24
2
Order By: Relevance
“…The inter serovars core genome size (3, 224 core genes) within the 35 Salmonella subsp. enterica was lower while the intra serovar core genome size (3, 836 core genes) for S. Typhimurium was higher compared to our analysis [76,77]. Low number of unique genes was directly related to the reduced genomes size, where HGT events were less and S. Bovismorbificans well correlated in this context with lowest numbers of unique genes and lower genome size.…”
Section: Discussioncontrasting
confidence: 59%
“…The inter serovars core genome size (3, 224 core genes) within the 35 Salmonella subsp. enterica was lower while the intra serovar core genome size (3, 836 core genes) for S. Typhimurium was higher compared to our analysis [76,77]. Low number of unique genes was directly related to the reduced genomes size, where HGT events were less and S. Bovismorbificans well correlated in this context with lowest numbers of unique genes and lower genome size.…”
Section: Discussioncontrasting
confidence: 59%
“…Furthermore, CRISPR-multi-virulence-locus sequence typing (MVLST) has been frequently used to subtype Salmonella serovars [10,11]. The conserved genetic organization of the cas genes in some Salmonella serovars is consistent with its biological function in these bacteria [12][13][14]. In addition, some reports found that in S. Typhi, this system consists of five transcriptional units, including two messenger ribonucleic acids (CRISPR-cas and cas3), one sense ribonucleic acid (scse2), and two antisense RNAs (ascse2-1 and ascas2-1) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Typhimurium isolates by a combination of variable-number tandem repeats (VNTRs) and clustered regularly interspaced short palindromic repeats (CRISPR) profiling called Repeats Typing has been used by Hiley et al 2014 [11] to recognise at least fifteen distinct genotypes. Whole genome sequencing (WGS) followed by core-genome single-nucleotide-polymorphism (SNP) analysis has supported the separation of strains into the same genotypes and determined the likely relationships between genotypes [12]. Genotyping has shown that there is a distinct divide between genotypes likely to have pSLT and those unlikely to have it.…”
Section: Introductionmentioning
confidence: 99%